If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20z + -33 = 40 Reorder the terms: -33 + 20z = 40 Solving -33 + 20z = 40 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '33' to each side of the equation. -33 + 33 + 20z = 40 + 33 Combine like terms: -33 + 33 = 0 0 + 20z = 40 + 33 20z = 40 + 33 Combine like terms: 40 + 33 = 73 20z = 73 Divide each side by '20'. z = 3.65 Simplifying z = 3.65
| 4(2x+4)+2(3x-5)= | | 9d-1d+2d-9=4d | | 2xy+5x=63 | | Z/10-5=6 | | 23-16.6=x | | x*x=16.6 | | -5+7x=7x+5 | | -5+12=47 | | 8(-2+x)-4x=32 | | 1/12-2/3m=1/3 | | 2a+7=4a-2 | | -4f+5=f+9f+5 | | x*x=14.6 | | 4(a+5)-2(a-5)= | | 12(x+3)=4(2x+9)+7x | | 5x/3-4=2x/5 | | 6g+2(4g-3)+10=32 | | 5=y+9 | | -30=-5/3(x=25) | | m/-4=5=14 | | -7r+6=-15 | | 5x-18=6x+8 | | f(x)=6x^3-53x^2-11x+2 | | .35y=15 | | 5x^2-lnx=0 | | -10-7m=-6m | | 3k+4=5k-10 | | 10+7p=24 | | 18x-8=13x-33 | | 2x-6+21=-3 | | -b-10=10+10+9b | | 4x-84=72-9x |